Visitor Circulation Analysis and Accessibility at Royal Plaza Mall Surabaya in the Comfort of Public Space - Miftahurahman, Rezaldy Andriansyah; Maharani, Rizka Tiara (RUAS, 2025)
Royal Plaza Mall Surabaya experiences significant increases in visitor numbers during weekends and holiday seasons. This tendency is leading to circulation congestion and limited accessibility. This study analyzes the relationships among circulation patterns, visitor accessibility, and public space comfort using a mixed-methods approach with a convergent parallel design. Quantitative data were obtained through escalator and elevator capacity evaluations using the Handling Capacity and Round Trip Time methods. Qualitative data were collected through field observations and thematic analysis supported by relevant literature. The findings indicate that the mall employs grid, linear, and radial circulation patterns; however, several areas, such as the 3rd-floor corridor, do not meet the required width for wheelchair users. Although escalators provide adequate capacity at 405,288 people/hour, the elevator capacity of 1,069 people/hour is insufficient during peak periods, requiring an additional 2-3 units. Furthermore, the accessibility design does not fully comply with PUPR standards, including the absence of a ramp at the main lobby. These results highlight the importance of integrating circulation patterns with accessible design to create a comfortable and inclusive public space.